Apoptotic Effect of Coix Polysaccharides on A549 Lung Cancer Cells in Vitro - Cheng LUO; Wei LIU; Xiangyi LU (Chinese Journal of Lung Cancer, 2012)
Background and objective Coix seeds are commonly used in Traditional Chinese Medicine and ingested through daily diet. The aim of this study is to analyze the apoptotic effect of coix polysaccharides on A549 cells. Methods A fraction of polysaccharides was isolated from coix seeds and extracted by ethanol precipitation. The extract was then purified by dialysis and DEAE-52 ion-exchange chromatography. Cell viability was determined by the MTT assay. Cell morphology was observed by scanning electronic microscopy (SEM), and cell cycle was detected by ﬂow cytometry (FCM). The relative quantities of caspase-3 and caspase-9 were determined by RT-PCR. Results Coix polysaccharides exerted remarkable inhibitory effects on A549 cell proliferation. Apoptotic bodies were observed by SEM. Apoptotic induction was also verified by DNA accumulation using propidium iodide nucleus staining in the S phase by ﬂow cytometry, as well as by DNA fragmentation using the comet assay. Regarding the molecular mechanism of apoptosis induction, the gene expression of caspase-3 and caspase-9 increased after coix polysaccharide treatment. Conclusion Polysaccharide fraction CP-1 induced A549 cell apoptosis.